경기지역 일부 고등학생의 식습관, 생활스트레스 및 영양지식과의 관계 - 박경애(Kyung Ae Park); 이홍미(Hongmie Lee); 송경희(Kyunghee Song) (Korean journal of community nutrition, 2020)
Objectives: This study was performed to examine dietary habits, life stress, and nutrition knowledge among high school students in Gyeonggi area. Methods: A total of 431 high school students (210 males, 221 females) in Gyeonggi area participated in this study from November to December of 2011. The study was a questionnaire-based survey that included dietary habits, dietary attitudes, life stress, and nutrition knowledge. Results: Body weight, height, and body mass index were all higher in male students than in female students (P < 0.001, respectively). For dietary habits, the average score (P < 0.01) and scores for considering combination of food groups (P < 0.05), eating green and orange vegetables (P < 0.05), eating meat, fish, eggs, or beans everyday (P < 0.05), drinking milk (P < 0.001), and eating seaweed (P < 0.01) were higher in male students than in female students. For dietary attitudes, the average score (P < 0.05) and scores for the five items were significantly different between male and female students. Male students showed a significantly lower nutrition knowledge score than female students (P < 0.05). Life stress score of students largely was attributable to academic factors, and female students showed higher stress score for academic, personal, and surrounding environmental (P < 0.05, respectively) factors than male students. Dietary habit score (P < 0.01) and nutrition knowledge score (P < 0.05) in female students as well as dietary attitude score (P < 0.05) in male students were negatively correlated with life stress score. Dietary habit scores in male and female students were positively correlated with dietary attitude score (P < 0.01, respectively). Need for nutrition education was significantly higher in female students than in male students (P < 0.05). Conclusions: This study provides basic information on dietary habits, dietary attitudes, life stress, and nutrition knowledge according to sex and suggests gender-specific practical nutrition education programs to address undesirable dietary habits and attitudes in students with higher stress levels.